Characterization of Industrial Pt-Sn/Al2O3 Catalyst and Transient Product Formations during Propane Dehydrogenation - Kah Sing Ho; Joanna Jo Ean Chye; Sim Yee Chin; Chin Kui Cheng (Bulletin of Chemical Reaction Engineering & Catalysis, 2013)
The major problem plaguing propane dehydrogenation process is the coke formation on the Pt-Sn/Al2O3 catalyst which leads to catalyst deactivation. Due to information paucity, the physicochemical characteristics of the commercially obtained regenerated Pt-Sn/Al2O3 catalyst (operated in moving bed reactor) and coke formation at different temperatures of reaction were discussed. The physicochemical characterization of regenerated catalyst gave a BET surface area of 104.0 m2/g with graphitic carbon content of 8.0% indicative of incomplete carbon gasification during the industrial propylene production. Effect of temperatures on coke formation was identified by studying the product yield via temperature-programmed reaction carried out at 500oC, 600oC and 700oC. It was found that ethylene was precursor to carbon laydown while propylene tends to crack into methane. Post reaction, the spent catalyst possessed relatively lower surface area and pore radius whilst exhibited higher carbon content (31.80% at 700oC) compared to the regenerated catalyst. Significantly, current studies also found that higher reaction temperatures favoured the coke formation. Consequently, the propylene yield has decreased with reaction temperature. © 2013 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)Corrigendum/Erratum of this article at: https://doi.org/10.9767/bcrec.9.2.7136.155